ANALISIS KESALAHAN PENGGUNAAN BAHASA DALAM TESIS MAHASISWA MAGISTER ADMINISTRASI PENDIDIKAN (Language Error Analysis Usage in Thesis of Education Administration Students Study Program, Post Graduate Program, Syiah Kuala University) - Maimunah, Maimunah (Universitas Muhammadiyah Aceh, 2013)
(1) spelling error in thesis of Education Administration Students Study Program, Post Graduate Program, Syiah Kuala University; (2) diction error in thesis of Education Administration Students Study Program, Post Graduate Program, Syiah Kuala University; (3) sentences error in thesis of Education Administration Students Study Program, Post Graduate Program, Syiah Kuala University. this research this researchThis research is qualitative approach.this research Kind of this research is descriptive research. Source of data in this research are thesis of Education Administration Students Study Program, Post Graduate Program, Syiah Kuala University. Primary instrument of this research is human instrument. Collecting data was done by (1) reading all souce of data; (2) identifying sentences error; (3) classifying error sentences which consist of spelling error, diction error, and sentences error. The result of this research shown that there are (1) spelling error, (2) diction error, and (3) sentences error in thesis of Education Administration Students Study Program, Post Graduated Program, Syiah Kuala University. Keywords: Error analysis, language, thesis of Education Administration students studi Program, Post Graduate Program, Syiah Kuala University DAFTAR PUSTAKA Ahmadi, Mukhsin. 1990. Strategi Belajar Mengajar Keterampilan Berbahasa dan Apresiasi Sastra. Malang. YA3 Malang. Akhadiah, Sabarti.2001. Materi Pokok Menulis I. Jakarta: Universitas Terbuka. Ali, Lukman. 1996. “Kita Punya Bahasa Nasional”. Kaki Langit, Sisipan Majalah Horizon. No. 1, Halaman 15. Alwi, Hasan dkk. 2003. Tata Bahasa Baku Bahasa Indonesia. Jakarta: Pusat Bahasa. Arifin, Zaenal. 2001. 1001 Kesalahan Berbahasa. Jakarta: Akademika Pressindo. Baradja, M.F. 1990. “Peranan Analisis Kontrastif dan Analisis Kesalahan dalam Pengajaran Bahasa”. Bahan Penataran Lokakarya Tahap II P3G. Depdikbud: Jakarta. Basuki, Imam Agus. 1995. “Analisis Kesalahan Berbahasa”. Modul IKIP Malang. Bloomfield, Leonard. 1995. Language: Bahasa. Terjemahan oleh I. Sutikno. Jakarta: PT Gramedia Pustaka Utama. Burt, M.K. 1975. “Error Analysis in The Adult EFL Classroom”. Dalam TESOL Quartely 9:53-63. Corder, S. Pit. 1974. Introduction Applied Linguistic. New York: Pingguin Books Ltd. Chaer, Abdul.2008. Tata Bahasa Praktis Bahasa Indonesia. Jakarta: Rineka Cipta. Ellis, Rod. 1980. Understanding Second Language Acquisition. Great Britain: Oxford University Press. . 1986. The Study of Second Language Acquiesition. Great Britain: Oxford University Press. Hamid, Fuad Abdul.1987. Proses Belajar Mengajar Bahasa. Jakarta: Ditjen Dikti. Depdikbud. Hendrickson, James M. 1980. “The Treatment of Error in Written Work”. Dalam Modern Language Journal 64: 216-21. Keraf, Gorys. 1994. Komposisi. Ende: Nusa Indah. . 2004. Diksi dan Gaya Bahasa. Jakarta: Gramedia Pustaka Utama. Kridalaksana, Harimurti. 2005. Kelas Kata dalam Bahasa Indonesia. Jakarta: Gramedia Pustaka Utama. Kushartanti, dkk. (ed.). 2005. Pesona Bahasa: Langkah Awal Memahami Linguistik. Jakarta: PT Gramedia Pustaka Utama. Miles, M.B. & M.A. Huberman. 1992. Analisis Data Kualitatif. Terjemahan oleh Tjetjep Rohandi. Jakarta: UI Press. Moleong, L.J. 2007. Metodologi Penelitian Kualitatif. Bandung: Remaja Rosdakarya. Muslich. Mansur. 1990. Garis-garis Besar Tata Bahasa Baku Bahasa Indonesia. Malang: YA3 Malang. Nurhadi. 1990. Bagaimana Meningkatkan Kemampuan Membaca. Bandung: CV Sinar Baru. Omagio, Alice C. 1986. Teaching Language in Context: Proficiency Oriented Instruction. Boston, Massachussetts: Heinle & Heinle Publishers. Pusat Bahasa. 2008. Kamus Besar Bahasa Indonesia. Jakarta: Pusat Bahasa Departemen Pendidikan Nasional. Richards, J. C. 1975. Errors Analysis Perspective on Second Language Acquaisition. London: Longman. Richards, J. C. & Willy A. R. 2002.Methodology in Language Teaching: An Anthology of Curent Practice. Cambridge: Cambridge University Press. Selinker, L. 1972. “Interlanguage”. Dalam International Review of Applied Linguistics 10:209-31. Samsuri.1993. Analisis Bahasa. Jakarta: Erlangga. Saussure, Ferdinand de.1993. Pengantar Linguistik Umum. Terjemahan oleh Rahayu S. Hidayat. Yogyakarta. Gajah Mada University Press. Sugihastuti. 2003. Bahasa Indonesia dari Awam, Mahasiswa, sampai dengan Wartawan. Yogyakarta: Gama Media. Sugiyono. 2008. Metode Penelitian Kuantitatif, Kualitatif, dan R & D. Bandung: Penerbit Alfabeta. Sugono, Dendy. 2003. Berbahasa Indonesia dengan Baik dan Benar. Jakarta: Puspa Swara. Syafi’ie, Imam. 1984. Analisis Kesalahan Berbahasa Dalam Karangan Mahasiswa di Tiga Perguruan Tinggi. Malang: IKIP Malang Press. Syafi’ie, Imam. 1988. Retorika dalam Menulis. Jakarta. Depdikbud. . 1994. Bahasa Indonesia Profesi. Malang: IKIP Malang Press. Tarigan, Henry Guntur, dan Tarigan, Djago. 1995. Pengajaran Analisis Kesalahan Berbahasa. Bandung: Angkasa.